O ensino de botânica e o ensino de ciências por investigação: contribuições na aprendizagem de alunos nos anos iniciais - Carvalho, Raquel Silva Cotrim (2021)
Teaching Science in a satisfactory way is the challenge of today's Basic Education teachers. Students are becoming increasingly digitally literate and show little interest in the lessons and content passed on in the traditional way. Teaching botany becomes even more complex, since, in general, the way teachers conduct their classes is far from the students' reality, with unattractive curricula, full of complex concepts and nomenclatures, far from the students' reality. Based on works described in the literature we can affirm that Science Teaching by Investigation has shown good results in Basic Education regarding teacher-student interaction, motivation, engagement, productivity and learning. Thus, we sought to identify how inquiry-based science teaching can contribute to the teaching of botany with a view to the learning of students in the early years of elementary school. In view of the proposed goals, the dissertation was divided into chapters that include systematic reviews of the literature that provided the necessary theoretical background for the analysis of results; the elaboration and application of Investigative Teaching Sequences (ISEs); the analysis of results after the application of the teaching sequences; and the elaboration of educational products. To elaborate the SEI's we used the Diagnostic Tool of Elements of Science Teaching by Investigation (DEEnCI) in order to ensure the investigative rigor in all the sequences. The SEI's were worked with 2nd grade students and the results were satisfactory. It was observed that students have a natural curiosity and investigative instinct, which facilitates the teaching-learning process, as well as the acquisition of significant learning. The main educational product consists of didactic material to support the teacher, with guidelines, images, and directions on how to apply the SEI's, from the introduction and survey of previous knowledge to the evaluation of learning. It is necessary to improve the studies on botany in the early years of elementary school in order to minimize botanical blindness.